An integrated chromatin accessibility and transcriptome landscape of human pre-implantation embryos - Longqi Liu (Nature Portfolio, 2019)
Early human embryonic development involves extensive changes in chromatin structure and transcriptional activity. Here the authors present LiCAT-seq, a method enabling simultaneous profiling of chromatin accessibility and gene expression with ultra-low input of cells and map chromatin accessibility and transcriptome landscapes for human pre-implantation embryos.